STUDENTS’ CONSCIOUSNESS ON LEARNING GRAMMAR IN ENGLISH TUTORIAL CLASS - Vilya Lakstian Catra Mulia (UIN Raden Mas Said Surakarta, 2017)
: Students in higher education are ordered to be competent in English. This happens as the response of high requirement in using English for larger uses nowadays. Consequently, higher education nowadays provides English tutorial to prepare the students to be competent English users, including mastering grammar. This research was conducted in order to discover students’ participation, grade, and score improvement as the aspects of applying consciousness towards English grammar.The research adopted mixed method approach. The researcher collected the data by observation, tests, and questionnaires. The participants were the students in English tutorial class from the Faculty of Islamic Economics and Business and the Faculty of Islamic Education and Teacher Training. The objective of this research are to monitor the students’ sincerity working on the learned lessons and to make senses their performance with the supports of their assessment records. The results showed various dynamics on the students’ existence being part in the lessons.High participation was done by the students along with various grades. All observed students showed positive self-correction and increasing score improvement with their heterogenous mechanisms.This research notices that the students have motivation to be mastered, but their experience and exposure on English grammar affect their assessment results. However, the data reveal that their efforts remain improved as reflected in their track records in the lessons.